Riemann type algebraic structures and their differential-algebraic integrability analysis - Prykarpatski, A.K.; Artemovych, O.D.; Popowicz, Z.; Pavlov, M.V. (Carpathian Mathematical Publications, 2010)
The differential-algebraic approach to studying the Lax type integrability of generalized Riemann type equations is devised. The differentiations and the associated invariant differential ideals are analyzed in detail. The approach is also applied to studying the Lax type integrability of the well known Korteweg-de Vries dynamical system.